Complete genome sequence of Mesorhizobium ciceri bv. biserrulae type strain (WSM1271T). Issue 3 (November 2014) - Nandasena, Kemanthi; Yates, Ron; Tiwari, Ravi; O'Hara, Graham; Howieson, John; Ninawi, Mohamed; Chertkov, Olga; Detter, Chris; Tapia, Roxanne; Han, Shunseng; Woyke, Tanja; Pitluck, Sam; et al.
Abstract Mesorhizobium ciceri bv.biserrulae strain WSM1271T was isolated from root nodules of the pasture legumeBiserrula pelecinus growing in the Mediterranean basin. Previous studies have shown this aerobic, motile, Gram negative, non-spore-forming rod preferably nodulatesB. pelecinus — a legume with many beneficial agronomic attributes for sustainable agriculture in Australia. We describe the genome ofMesorhizobium ciceri bv.biserrulae strain WSM1271T consisting of a 6, 264, 489 bp chromosome and a 425, 539 bp plasmid that together encode 6, 470 protein-coding genes and 61 RNA-only encoding genes.